Aspects of Langerhans cells and TNF-α in the cutaneous immunity of anogenital warts, - John Verrinder Veasey; Adriana Bittencourt Campaner; Rute Facchini Lellis (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Anogenital warts are the leading sexually transmitted infection in patients seeking care at specialized clinics. They may display a vast array of forms, according to the interaction of the virus with the host's immunity. Cellular immunity is the epithelium's main form of defense against the virus, involving an active participation of the Langerhans cells and pro-inflammatory cytokines such as TNF-α. Objective: To assess the epithelial immune response of anogenital warts in males, according to the number of lesions presented. Methods: This is a prospective, cross-sectional study carried out at the dermatology outpatient clinic in a tertiary hospital. We included male patients over 18 years of age without comorbidities who had anogenital condylomata and no previous treatments.In order to evaluate the local epithelial immunity, the lesions were quantified, then removed and employed in CD1a immunohistochemistry assays for assessing the morphometry and morphology of Langerhans cells; TNF-α; reaction was used for determining cytokine positivity in the epithelium. Results: 48 patients were included in the study. There was no statistically significant difference as to the number of Langerhans cells, in their morphology, or the presence of TNF-α. However, patients presenting with more Langerhans cells in the lesions had cells with a star-like and dendritic morphology, whereas in those with a lower cell count had cells with a rounded morphology and no dendrites (p < 0.001). Study limitations: Small number of patients analyzed. Conclusion: There was no difference in epithelial immunity between patients having few or many anogenital condyloma lesions as measured by the morphology and morphometry of Langerhans cells and TNF-α; positivity. Such an assessment employing immunity markers differing from the usual ones is expected to yield useful results.